Pengaruh Kompetensi, Soft Skill, dan Pengalaman Magang Terhadap Kesiapan Kerja Mahasiswa Universitas Muhammadiyah Sidoarjo - Vionalita Dheanisa; Dewi Andriani; Rifdah Abadiyah (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
Indonesian universities face challenges in producing competent and competitive graduates in the workforce. Based on tracer study data from the University of Muhammadiyah Sidoarjo, the graduation rate is still below 50%. This is known to be due to less than optimal work readiness. This study aims to determine how competency, soft skills, and internship experience affect the work readiness of students at the University of Muhammadiyah Sidoarjo. This study used a quantitative approach with a sample of 138 active students in the management study program at the University of Muhammadiyah Sidoarjo. The results showed that competency, soft skills, and internship experience simultaneously had a significant effect on the work readiness of students at the University of Muhammadiyah Sidoarjo. Data were analyzed using multiple linear regression using the SPSS program.